Effect of changes in the net height, court size, and serve limitations on technical-tactical, physical, and psychological aspects of U-14 female volleyball matches - Palao, Jose M.; Ureña, Aurelio; Moreno, Maria P.; Ortega-Toro, Enrique (Frontiers in Psychology, 2024)
The objective was to analyze the effect of a reduction of the net height and the court size and serve limitations on the technical-tactical actions, physical actions, and psychological aspects in youth volleyball players. The sample was 29 under-14 female volleyball players (three regional club teams). A quasi-experimental design was implemented to assess the effect of modification in three tournaments. The independent variables were: a) official rules tournament (no changes in the rules), b) Experimental Tournament 1 (reduction in the net height from 2.10 m to 2 m, no jump serves, and a maximum of two serves per player and rotation), and c) Experimental Tournament 2 (reduction in net height from 2.10 m to 2 m, reduction in court size from 9x9m to 8x8m, no jump serves, and a maximum of two serves per player and rotation). The dependent variables were: ball contact done (type), quality and efficacy of the technical actions, team game phases occurrence, quality and efficacy, continuity index, number of jumps, player's jump load in the take-off and landing, number of hits, average heart rate, Rate of Perceived Effort, time between ball contacts, serve velocity, perceived individual and collective self-efficacy, perceived enjoyment, and perceived satisfaction. Experimental Tournament 1 involved an increase in the efficacy of serves and a decrease in the efficacy of side-out phases. The imbalance between serve and reception did not impact game continuity but reduced the attack and blocks. Experimental Tournament 2 involved a decrease in the efficacy of serves and an increase in the efficacy of side-out phases. The balance between serve and This is a provisional file, not the final typeset article reception increased reception efficacy, the occurrence of attacks and blocks, game continuity, and players' effort. At the psychological level, none of the experimental tournaments involved changes regarding players' individual or collective self-efficacy, perceived enjoyment, or perceived satisfaction with regard to the control tournament.